Pengaruh Brand Awareness dan Influencer Tasya Farasya terhadap Brand Trust Produk Skintific - Tania, Maria Cindy; Delliana, Santi; Vardiansyah, Dani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Brand trust is an important thing that the company must pursue. This is because brand trust is closely related to the company's existence. This research was conducted aiming to find out whether there is influence of Brand Awareness and influencer Tasya Farasya on Brand Trust of SKINTIFIC Products. Researchers refer to the theory of communication persuasion matrix to analyze the concept. The method used in this research is quantitative with explanatory research. Technique The sample in this study was calculated using purposive sampling. The results of this study indicate that brand awareness and influencer Tasya Farasya has a positive and significant effect on brand trust. The independent variable simultaneously influences the dependent variable by 81.9%.